Should I stay or should I go? Why nurses are leaving community nursing in the UK - Michaela Senek; Steve Robertson; Rachel King; Emily Wood; Tony Ryan (BMC, 2023)
Abstract Worsening working conditions for nursing workforce has seen a massive exodus of staff, particularly in community nursing in the UK. Aim: The study aim was to map working conditions as well as identify differentiating characteristics of community nurses that intend to leave their profession. Design: Eligibility criteria were community nurses working in all 4 UK countries. All data was collected by means of a cross-sectional survey via the largest closed, private community nursing online-forum. Logistic regression was carried out to ascertain the effects of the variables on the intention to leave. Results: The total number of respondents was 533. Findings showed that one in two of all community nurses (≈46%) are reporting job dissatisfaction. Length of unpaid overtime per shift (odds increase by 30% for each hour of overtime), manager support, proportion of permanent staff, team size, shift length, travel mileage, worsened conditions in the last year and overall self-rated working conditions were differentiating factors between those that intended to leave the job. The proportion of permanent staff on the team and perceived lack of support from management best predicted the likelihood of leave rates. Our findings imply that low nurse retention will fuel an even higher exodus because job dissatisfaction is highest on teams with lowest permanent staff ratios. Poor management that is inept at supporting frontline staff means that the fundamental retention issues are exacerbated and will not stop the unprecedented crisis that is predicted to lead to a collapse of care provision in community settings. Nurses play a central role and are 'key' to delivering the much- desired patient-centred care' therefore their well-being and job satisfaction should become a priority for policymakers.